Logarithms!

Calculus Level 3

0 1 ln x d x + 1 0 ln ( x + 1 ) d x = ? \large \int_0^1 \ln x \, dx + \int_{-1}^0 \ln(x+1) \, dx = \, ?


The answer is -2.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

For 0 1 ln x d x + 1 0 ln ( x + 1 ) d x \int_{0}^{1} \ln x\,dx + \int _{-1}^{0} \ln \left(x+1\right)\,dx

0 1 ln x d x + 1 0 ln ( x + 1 ) d x = [ x ln ( x ) x + C ] 0 1 + [ x + ( x + 1 ) ln ( x + 1 ) 1 + C ] 1 0 Indefinite* = [ 1 0 ] + [ 1 0 ] = 2 \begin{aligned} \int_{0}^{1} \ln x\,dx + \int _{-1}^{0} \ln \left(x+1\right)\,dx &= [x \ln(x)-x \color{grey}{\ce{+C}}]_{0}^{1}+[-x+(x+1) \ln(x+1)-1 \color{grey}{+\ce{C}}]_{-1}^{0} \quad\quad\quad{\text{Indefinite*}}\\& =[-1-0]+[-1-0] \\&= -2 \space \square \end{aligned}


*For clarification by computing definite integrals you have to remove the constant ( + C +\ce{C} ) after you integrate to avoid confuse.

ADIOS!!! \large \text{ADIOS!!!}

Very nice. But how did you get your last second step?

Akash Shukla - 5 years ago

Log in to reply

Use the definite formula

a b f ( x ) d x = F ( b ) F ( a ) \int_{a}^{b} f(x)\,dx = F(b) - F(a)

OK! \displaystyle{\text{OK!}}

Log in to reply

Haha.. thank you. But by doing this we get 0*log(0), which is not defined

Akash Shukla - 5 years ago

Log in to reply

@Akash Shukla For the second step of [ x ln ( x ) x + C ] 0 1 + [ x + ( x + 1 ) ln ( x + 1 ) 1 + C ] 1 0 \ [x \ln(x)-x \color{grey}{\ce{+C}}]_{0}^{1}+[-x+(x+1) \ln(x+1)-1 \color{grey}{+\ce{C}}]_{-1}^{0} you have to remove the constant

were

[ x ln ( x ) x + C ] 0 1 + [ x + ( x + 1 ) ln ( x + 1 ) 1 + C ] 1 0 [x \ln(x)-x \color{grey}{\ce{+C}}]_{0}^{1}+[-x+(x+1) \ln(x+1)-1 \color{grey}{+\ce{C}}]_{-1}^{0}

for

[ x ln ( x ) x ] 0 1 = x ln ( x ) Apply L’H o ˆ pital’s Rule = ( ln ( x ) 1 x ) 0 1 = ( d d x ( ln ( x ) ) d d x ( 1 x ) ) 0 1 = ( 1 x 1 x 2 ) 0 1 Reciprocal = ( x ) 0 1 Substitute = ( 1 ) 0 = 1 \begin{aligned} [x \ln(x)-x]_{0}^{1} &=x \ln(x) \quad{\text{Apply L'Hôpital's Rule}} \\&= \left(\frac{\ln(x)}{\frac{1}{x}}\right)_{0}^{1} \\&= \left(\frac{\frac{d}{dx}(\ln(x))}{\frac{d}{dx}\left(\frac{1}{x}\right)}\right)_{0}^{1} \\&= \left(\frac{\frac{1}{x}}{-\frac{1}{x^2}}\right)_{0}^{1} \quad\quad\quad\quad{\text{Reciprocal}} \\&= (-x)_{0}^{1} \quad\quad\quad\quad{\text{Substitute}} \\&=(-1) - 0 = -1 \end{aligned}

and

( x + ( x + 1 ) ln ( x + 1 ) 1 ) 1 0 = ( ( 0 ) + ( ( 0 ) + 1 ) ln ( ( 0 ) + 1 ) ) ( ( 1 ) + ( ( 1 ) + 1 ) ln ( ( 1 ) + 1 ) ) = 1 \begin{aligned}(-x+(x+1) \ln(x+1)-1)_{-1}^{0} &= ((0)+((0)+1) \ln((0)+1))-((-1)+((-1)+1)\ln((-1)+1)) \\&=-1\end{aligned}

where [ x ln ( x ) x + C ] 0 1 + [ x + ( x + 1 ) ln ( x + 1 ) 1 + C ] 1 0 = 2 \left[x \ln(x)-x \color{grey}{\ce{+C}}\right]_{0}^{1}+\left[-x+(x+1) \ln(x+1)-1 \color{grey}{+\ce{C}}\right]_{-1}^{0} = -2 \square

ADIOS!!! \LARGE\text{ADIOS!!!}

Log in to reply

@A Former Brilliant Member Thank you. Actually I don't know about this, so I have questioned on your solution.

Akash Shukla - 5 years ago

Log in to reply

@Akash Shukla Asking is a principal interaction of conversation.

@Akash Shukla L'Hôpital's Rule rule helps solve that problem.

tytan le nguyen - 5 years ago

Log in to reply

@Tytan Le Nguyen I'm sorry I forgot using L'Hôpital's rule thank you for recalling that.

@Tytan Le Nguyen That rule is useful on limits. But how to use that L'Hôpital's Rule on integration?

@Akash Shukla Actually 0 L O G 0 ( x ) = 0\ce{LOG}_{0}(x)=\infty .

Log in to reply

@A Former Brilliant Member I have done it by expansion of log. The method you suggested involves 0 l o g ( 0 ) 0*log(0) , which is not defined.

Akash Shukla - 5 years ago

Aren't the two integrals the same value since they're the same functions, only one is translated left one unit (along with the limits of integration)? If that is true then you should just have to multiply the first one by 2 instead of writing out the entire second antiderivative.

Ryan Kelly - 5 years ago

Log in to reply

Yes, they both are same

Akash Shukla - 5 years ago

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...